KOMUNIKASI PERSUASIF YAYASAN SAHABAT CINTA UMAT MENARIK MINAT (INTEREST) DALAM MENSOSIALISASIKAN SEDEKAH MINYAK JELANTAH PADA PROGRAM LIMBAH JADI SEDEKAH DI KOTA PEKANBARU - Yessica Muslim; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The Sahabat Cinta Umat Foundation through the Waste So Alms Program in Pekanbaru City seeks to influence the community to be able to give alms through used cooking oil so that no used cooking oil is dumped into the environment. The efforts of the Sahabat Cinta Umat Foundation are very appropriate when observed with a persuasive communication model, namely the AIDDA model. The purpose of this study was to determine the Persuasive Communication of the The Sahabat Cinta Umat Foundation to build attention, interest, desire, decision and action in disseminating used cooking oil alms in Pekanbaru City. This type of research is a qualitative research that goes directly to research into the research location. This research is qualitative in nature and is descriptive in nature to tell the real thing that is in the field. The location of this research was carried out at The Sahabat Cinta Umat Foundation, Pekanbaru City. The subjects of this research are the Chairperson of The Sahabat Cinta Umat Foundation, the Secretary/Administration, working members of the Waste So Alms program and contributors of used cooking oil from business actors, housewives, or the general public. The object of the research is the Persuasive Strategy of the Friends of the Love of the People Foundation in Disseminating the Alms of Cooking Oil. Data collection techniques using observation, interviews and documentation. In the process of data analysis, the researchers used an interactive analysis model. The results showed that the socialization of the Used Cooking Oil Alms program in the Waste So Alms Program in Pekanbaru City was good, it can be seen from the beginning of the used cooking oil alms program, the cooperation partners helped by procuring containers as a place to collect used cooking oil, then the cooperation partners to date still assisting in this program and adding to the broad reach of this program. Keywords: Persuasive Communication, Wasre So Alms Program